Developing Microlearning Video-Based Discovery Learning in English Classroom at Vocational High School - Ditha Saitri, I Gusti Ayu; Kerti Nitiasih, Putu; Hery Santosa, Made (Institut Agama Islam Negeri Palopo, 2025)
The study aimed at developing a microlearning video-based discovery learning for teaching English at SMK Pariwisata Nusadua Sidemen. The development was conducted by adopting SAM model. There were three stages; preparation, iterative design, and iterative development. The research subjects were three English teachers and 30 eleventh-grade students at SMK Nusadua Sidemen. The sampling techniques used were purposive and simple random sampling. The data were obtained by conducting an interview, a survey, and document analysis. The research instruments were interviewing guide, questionnaire, and note. The result revealed that the microlearning video-based discovery learning was developed for teaching the expression of asking and giving opinion with good category.